Surfactant-free synthesis of ellipsoidal and spherical shaped TiO2 nanoparticles and their comparative photocatalytic studies. Issue 4 (August 2017) - Ali, Shahid; Khan, Safyan A.; Khan, Ibrahim; Yamani, Zain H.; Sohail, Manzar; Morsy, Mohamed A.
Graphical abstract: Highlights: Surfactant-free synthesis of ellipsoidal and spherical TiO2 NPs. Control shape and size of TiO2 NPs under mild reaction conditions. Comparative photocatalytic studies of synthetic and commercial TiO2 NPs. Decolorization and TOC removal of non-biodegradable organic pollutants. Ellipsoidal TiO2 NPs exhibit superior photocatalytic activity than other forms. Abstract: The work presents surfactant-free synthesis of ellipsoidal and spherical TiO2 nanoparticles (NPs) and their photocatalytic activities are compared with commercially available cubic shaped titania. The ellipsoidal TiO2 NPs having average length of ∼21 nm and width ∼10 nm were synthesized via a facile solvothermal method. The spherical TiO2 NPs were prepared by the solvent evaporation method having average diameter of ∼8 nm. We effectively control the shape and size of TiO2 NPs under mild reaction conditions without using any surfactant. XRD patterns show diffraction peak at 25.3° corresponding to (1 0 1) crystalline plane, which confirmed the anatase phase of TiO2 NPs. BET surface area of the ellipsoidal and spherical TiO2 NPs are 2.22 and 1.85 times higher than cubic TiO2, respectively. Kubelka–Munk plots demonstrate significant decrease in the band gap of ellipsoidal (3.0 eV) and spherical (3.17 eV) NPs as compared to cubic shaped TiO2 (3.24 eV). The photocatalytic activities of these materials investigated by decolorization/removal of rhodamine-6G (R6G) and methylene blue (MB) under UV–visible light irradiation. In first 15 min of photo-degradation experiments, the results indicated 98, 86 and 71% decolorization and 90, 80 and 60% total organic carbon (TOC) removal of R6G by ellipsoidal, spherical, and cubic shaped TiO2 NPs, respectively. Similar findings were obtained for the photo-degradation of MB solution. This confirms the superior photocatalytic characteristics of the ellipsoidal NPs among the reported TiO2 shapes.